Impact Of Quality Improvement Practices On Patient Safety And Patient Satisfaction In Primary Health Care Centers And Hospitals In The Makkah Region A Multidisciplinary Cross-Sectional Analysis Of Published National Evidence (The Review of Diabetic Studies, 2024)
Quality Improvement (QI) techniques are pivotal in influencing patient safety and satisfaction within healthcare systems.  This study consolidates recent data from Saudi Arabia, namely the Makkah Region, to assess the impact of quality improvement-related factors on safety culture and patient satisfaction in primary health care centers and hospitals.  National data from the Ministry of Health’s Patient Experience Measurement Program (n = 536,406) revealed elevated satisfaction levels in PHCCs (mean = 4.2/5; 83.8%), with care provider domains attaining the highest scores (84.8%).  Regional studies indicated variability: in Aseer PHCCs, satisfaction levels ranged from 14.9% to 33%.  The data on patient safety culture from Makkah indicated a composite positive response rate of approximately 62% at King Abdullah Medical City, markedly lower than the global standard of 70%.  Systematic reviews revealed significant obstacles to safety culture, such as punitive reactions to errors, excessive workload, and deficiencies in communication.  In all research, quality improvement categories such as cooperation, organizational learning, communication, and adherence to guidelines consistently forecasted enhanced safety culture and patient satisfaction.  These findings underscore the necessity for enhanced system-level quality improvement initiatives in the Makkah Region, particularly in incident reporting and service flow optimization.